The scandal of the evangelical mind - Noll, Mark A., 1946- (Grand Rapids, Mich. : W.B. Eerdmans, 1994)
"The scandal of the evangelical mind," says historian Mark Noll, "is that there is not much of an evangelical mind." This critical yet constructive book explains the decline of evangelical thought in North America and seeks to find, within evangelicalism itself, resources for turning the situation around.
According to Noll, evangelical Protestants make up the largest single group of religious Americans; they also enjoy increasing wealth, status political influence, and educational achievement.
Yet, despite its size and considerable intellectual potential, evangelical Protestantism makes only a slight contribution to first-order public discourse in North America: it neither sponsors a single research university, nor supports a single periodical devoted to in-depth interaction with modern culture, nor cultivates attitudes that treat the worlds of science, the arts, politics, and social analysis with the seriousness that God intends.
The Scandal of the Evangelical Mind explains how this situation developed by tracing the history of evangelical thinking in America. Noll's analysis shows how Protestants successfully aligned themselves with national ideals and with the particular expressions of an American Enlightenment in the decades before the Civil War; explains how fundamentalists at the start of the twentieth century preserved essential elements of the faith, but only by grievously damaging the life of the mind; gives specific attention to evangelical thought on politics and science; and discusses what some have called an "evangelical intellectual renaissance" in recent decades and shows why it is more apparent than real.
1. The Contemporary Scandal -- 2. Why the Scandal Matters -- 3. The Evangelical Mind Takes Shape - Revival, Revolution, and a Cultural Synthesis -- 4. The Evangelical Enlightenment -- 5. The Intellectual Disaster of Fundamentalism -- 6. Political Reflection -- 7. Thinking about Science -- 8. Is an Evangelical Intellectual Renaissance Underway? -- 9. Can the Scandal Be Scandalized?
Includes bibliographical references and index.
Keywords: Evangelicalism -- United States; Christianity -- United States -- Forecasting; Christianity and culture